PEMANFAATAN LIMBAH INDUSTRI PENGGERGAJIAN DAN STIK ES KRIM PADA PEMBUATAN MINIATUR RUMAH ADAT BANJAR “GAJAH MANYUSU” - Rizky Pratama; Kurdiansyah Kurdiansyah; Adi Rahmadi (Universitas Lambung Mangkurat, 2022)
Making a miniature design of the Banjar traditional house “Gajah Manyusu” using raw materials from sawn wood waste and Analyzing production costs in the manufacture of miniature of Banjar traditional house “Gajah Manyusu”. Data analysis on the manufacture of banjar traditional houses miniature includes several stages of economic analysis, namely calculating the total cost of raw materials, calculating manufacturing costs, return on investment, analysis of production costs, analysis of revenue and income, analysis of the revenue-cost ratio (revenue-cost ratio). Analysis of the percentage use of waste in miniature, Analysis of the percentage of use of waste in miniature. The manufacture of Banjar traditional house miniature “Gajah Manyusu” mostly comes from sawn cut waste material from the Banjarbaru forestry faculty workshop and the costs incurred for its manufacture are quite cheap. The waste raw materials include sawn pieces and pieces of plywood which are then used as floor and roof frameworks in miniature buildings, while the walls use duplex paper as raw material, which makes building walls much easier. The tools used in the manufacture of miniatures have a relatively long service life depending on the quality of the tools used so that the depreciation costs are relatively small. This miniature of Banjar traditional house Gajah Manyusu is rectangular in shape, one of the characteristics of this traditional house is that the roof is in the form of a stump or nose shield that covers the entire building, then over time there are additional platforms on the right and left of the building for the roof itself does not use a stump roof, but an arch roof.Membuat rancangan miniatur rumah adat Banjar Gajah Mayusu dengan menggunakan bahan baku dari limbah kayu gergajian dan Menganilisis biaya produksi pada pembuatan miniatur rumah adat Banjar Gajah Manyusu. Menghitung total biaya bahan baku, menghitung biaya pembuatan, Pengembalian investasi, Analisis biaya produksi, analisis penerimaan dan pendapatan, analisis rasio penerimaan-biaya (revenue-cost ratio).Pembuatan miniatur rumah adat banjar gajah manyusu ini sebagian besarnya berasal dari bahan limbah potongan gergajian yang berasal dari workshop fakultas kehutanan banjarbaru dan biaya yang dikeluarkan untuk pembuatannya terbilang cukup murah. Bahan baku limbah tersebut antara lain potongan bekas gergajian dan potongan plwood yang kemudian dimanfaatkan sebagai kerangka lantai dan atap pada bangunan miniatur, sedangkan pada dinding menggunakan bahan baku kertas duplex yang mana dengan menggunakan bahan tersebut pembuatan bangunan dinding jauh lebih mudah. Alat yang digunakan pada pembuatan miniatur memiliki umur pakai yang relatif lama tergantung dengan kualitas alat yang digunakan sehingga biaya penyusutan relatif kecil. Miniatur rumah adat banjar gajah manyusu ini berbentuk persegi panjang, salah satu ciri khas pada rumah adat ini yaitu pada atapnya berbentuk perisai buntung atau hidung bapicik yang menutupi hingga seluruh bangunan, kemudian selang berjalannya waktu terjadi penambahan anjung pada bagian kanan dan kiri bangunan untuk bagian atap sendiri tidak menggunakan atap perisai buntung melainkan atap sengkuap.